Фундаментальні орієнтири в румунській фольклористиці - Константінеску, Н. (Народна творчість та етнологія, 2011)
A brief study of the history of the Romanian folkloristics reveals three leading scholars in that field before the mid-20th century: B. P. Hasdeu, O. Densusianu, and D. Caracostea. The centennial of the first lesson of folklore delivered at the Faculty of Letters of the University of Bucharest by the second of the three aforementioned scholars, O. Densusianu, was celebrated in 2009. Following the roads paved by his predecessors and mentors, M. Pop elucidated the field of folkloristics further and proposed new directions in the study of folk-literature in particular and folk culture at large. O scurtă trecere în revistă a istoriei folcloristicii româneşti evidenţiază trei figuri conducătoare ale disciplinei până în a doua jumătate a secolului al XX‑lea: B. P. Haşdeu, O. Densuşianu şi D. Caracostea. Centenarul primei lecţii de folclor ţinută la Facultatea de Litere a Universităţii din Bucureşti de către cel de-al doilea dintre cei trei savanţi menţionaţi mai sus, O. Densuşianu, a fost celebrat în 2009. Mergând pe drumurile deschise de predecesorii şi maeştrii săi, M. Pop a propus noi direcţii în studiul literaturii populare şi a culturii populare în general.